ERROR ANALYSIS OF HIGH SCHOOL STUDENTS ON LINEAR PROGRAM TOPICS BASED ON NEWMAN ERROR ANALYSIS - Elsa, Hanne Ayuningtias; Sudihartinih, Eyus (Study Program of Mathematics Education University of Muhammadiyah Malang, 2020)
This study aims to obtain a description of the errors of high school students on linear program topics by using the Newman Error Analysis. This type of research is a descriptive study with a qualitative approach. This research was conducted by giving a test to participants consisting of a three-word problem on the topic of a linear program then conducting interviews as a data collection technique. Participants in this study were five female students of class XI in one of the senior high schools in Bandung, including four people who were students majoring in Sciences studies and one person who was a student majoring in Social studies. Based on the results of a research according to the Newman Error Analysis, all participants made several types of errors on the topic of a linear program. Errors made by the participants include transformation errors made by three students, the process skill errors made by two students, and writing error answers made by two students.